2015
DOI: 10.1088/0264-9381/32/19/195018
|View full text |Cite
|
Sign up to set email alerts
|

Embeddings for general relativity

Abstract: We present a systematic approach to embed n-dimensional vacuum general relativity in an (n + 1)-dimensional pseudo-Riemannian spacetime whose source is either a (non)zero cosmological constant or a scalar field minimallycoupled to Einstein gravity. Our approach allows us to generalize a number of results discussed in the literature. We construct all the possible (physically distinct) embeddings in Einstein spaces, including the Ricci-flat ones widely discussed in the literature. We examine in detail their gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 62 publications
(197 reference statements)
2
32
0
Order By: Relevance
“…This situation was also encountered by Ray et al (2007) who considered a dark energy model with Λ = 3αH 2 (see also Arbab 1997;Singh et al 1998;Ponce de Leone 2003), under the assumption that G is also time dependent, and showed that comparison with most observations requires a negative value of α.…”
Section: Discussionsupporting
confidence: 51%
“…This situation was also encountered by Ray et al (2007) who considered a dark energy model with Λ = 3αH 2 (see also Arbab 1997;Singh et al 1998;Ponce de Leone 2003), under the assumption that G is also time dependent, and showed that comparison with most observations requires a negative value of α.…”
Section: Discussionsupporting
confidence: 51%
“…It is worth noting that in establishing the IMT [4], or even the modified scalar-tensor theories, see, e.g., [9], an apparent vacuum 2 bulk has been considered. However, in this work, we would establish a more extended version of a reduced theory by taking a non-vanishing energy momentum tensor, L (D+1) matt = 0.…”
Section: Modified Sáez-ballester Scalar-tensor Theory In Arbitrarmentioning
confidence: 99%
“…It has been shown that the classical tests of general relativity and the experimental limits on violation of the equivalence principle do not disqualify any higher dimensional theories of gravity [5][6][7]. Concerning astrophysical/cosmological applications, such induced sectors or their extensions can play the role of either ordinary matter, dark matter or dark energy [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The famous Friedman-Robertson-Lemaitre space-time, is of class p = 1, while the Schwarzschilds exterior and interior solutions are of class p = 2 and class p = 1 respectively, moreover Kerr metric is class 5. In the literature [42][43][44][45][46][47][48][49], there are many interesting work concerning the effects of the technique of embedding of lower dimensional Riemannian space into the higher dimensional pseudo-Euclidean space in the framework of GR. The main consequence of embedding a Riemannian variety corresponding to a spherically symmetric and static spacetime into a pseudo Euclidean space is the so-called Eisland condition.…”
Section: Introductionmentioning
confidence: 99%